2 Tenn. Comp. Stat. 125, tit. 12, ch. 9, art. 2, § 4864 - (:unkn) unknown (General Publisher, 1856)
Any person who sells, loans, or gives, to any minor a pistol, bowie-knife, dirk, Arkansas tooth-pick, hunter’s knife, or like dangerous weapon, except a gun for hunting or weapon for defense in traveling, is guilty of a misdemeanor, and shall be fined not less than twenty-five dollars, and be imprisoned in the county jail at the discretion of the court.
--
Keywords: TRANSFER - MINORS